A COMPARATIVE ANALYSIS OF PRE-ENGINEERED AND CONVENTIONAL STEEL BUILDINGS: DESIGN, CONSTRUCTION, COST, AND PERFORMANCE (International Journal of Engineering Management Science, 2024)
This review paper provides a comprehensive comparative analysis of pre-engineered buildings (PEBs) and conventional steel buildings. The comparison is based on various aspects including design, construction, cost, and performance. The paper begins with an introduction to PEBs and conventional steel buildings, highlighting their key characteristics and importance in the construction industry. It then explores the structural design principles, design methodologies, and standards for both building types. The construction processes, speed of construction, ease of assembly, and quality control measures are also compared. Cost analysis is a significant focus, including the initial cost comparison, life-cycle cost considerations, and factors affecting cost differences between PEBs and conventional steel buildings. Additionally, the paper examines the structural performance undervarious loads (wind, snow, seismic), durability, maintenance requirements, energy efficiency, and environmental impact of both building types.
Keywords: Pre-engineered buildings, conventional steel buildings, comparative analysis, design, construction, cost, performance.